Pengaruh Brand Personality, Perceived Quality, dan Word Of Mouth Terhadap Keputusan Pembelian (Study pada Konsumen Beli Kopi Kecamatan Pandaan) - Akbar, Mohammad Aziz; M. Sulhan (Jurnal Administrasi Bisnis Nusantara, 2026)
This study aims to determine the influence of Brand Personality, Perceived Quality, and Word of Mouth on Purchase Decisions among Belikopi consumers in Pandaan District. This research uses a quantitative approach with a survey method through questionnaire distribution. The population in this study consists of Belikopi consumers, with a total sample of 107 respondents selected using purposive sampling technique. The data used is primary data and analyzed using multiple linear regression with the help of SPSS. The results of the study show that: Brand Personality, Perceived Quality, and Word of Mouth has a positive and significant partial effect on Purchase Decision; and Simultaneously, Brand Personality, Perceived Quality, and Word of Mouth have a significant effect on the Purchase Decision of Belikopi consumers